Herbivore insects and predatory arthropods in freshwater swamp rice field in South Sumatra, Indonesia sprayed with bioinsecticides of entomopathogenic fungi and abamectin - Siti Herlinda; Ghanni Prabawati; Yulia Pujiastuti; Susilawati Susilawati; Tili Karenina; Hasbi Hasbi; Chandra Irsan (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Herlinda S, Prabawati G, Pujiastuti Y, Susilawati, Karenia T, Hasbi, Irsan C. 2020. Herbivore insects and predatory arthropods in freshwater swamp rice field in South Sumatra, Indonesia sprayed with bioinsecticides of entomopathogenic fungi and abamectin. Biodiversitas 21: 3755-3768. Herbivore insect population and predatory arthropods in rice field may be effected by the application entomopathogenic fungi or synthetic insecticide. The objective of this research was to analyze individual quantity of herbivore insects and predatory arthropod inhabiting freshwater swamp rice fields treated with bioinsecticides and abamectin (commercial insecticide). This research was conducted in the freshwater swamp rice field located in Village Pelabuhan Dalam, Sub District Pemulutan, District Ogan Ilir, and South Sumatra. The experiment was arranged in a Completely Randomized Block Design consisted of four plots of treatment. The research used the bioinsecticides made from entomopathogenic fungi (Beauveria bassiana, Metarhizium anisopliae, and Cordyceps military), and abamectin. Sampling to collect arthropods inhabiting rice canopy was also conducted using an entomological net in the study locations. This research found 12 families of herbivore insects with 22 species dominated by Nilaparvata lugens and Leptocorisa acuta and 32 species of spider belonged to eight families dominated by Tetragnatha virescens and Oxyopes matiensis. The species diversity of spider was higher in the plots of the bioinsecticide compared to that of the abamectin. Predatory insects found belonged to 14 species belonged to eight families dominated by species of Ophionea nigrofasciata, Verania discolor, and Paedorus fuscipe. The abundance of predatory insects in plots sprayed with the bioinsecticides was higher compared to that of the abamectin plot. The abundance and species diversity of predatory arthropod sprayed with bioinsecticide of B. bassiana, M. anisopliae, and C. militaris did not decrease, while the population of herbivore insect tended to decrease.